(untitled) (REVISTA NODO, 2019)
Global concern about the management of water and its sources is product of the environmental crisis of the modern world, since water is one of the constituent elements of life and living beings. Colombia is no stranger to such concern, since being a country with a great water wealth, this does not exempt it from being contaminated by various physicochemical and biological factors, which could cause harm not only to humans but also to ecosystems where they are, which can lead to gradually losing their quality of life. For this reason, the present research sought to identify the physicochemical contaminants elements present in the Cañafístula stream of the municipality of Polonuevo, Atlantic. The study was carried out using a type of descriptive research with a mixed approach under an interpretive hermeneutic paradigm. Observations were used as a technique for collecting the information and the laboratory tools for analysis and sampling. The sample consisted of sampling points from the Cañafistula stream in the municipality of Polonuevo, strategically located from the beginning of the stream to the end. The results showed that there are physicochemical agents outside the parameters allowed in the product standard, produced by the residents of the municipality and of the farms that surround it, without evidencing contaminating levels of contamination, when not evidencing that treated in a timely manner, would affect the population.